Search Coil-Based Startup Angle and Rotor Position Estimation for Enhanced Full-Speed-Range Motor Drives - Hsien-Yuan Hsu; Min-Fu Hsieh (IEEE Access)
This study presents a fully integrated motor drive system capable of full-speed-range operation by employing a rotor angle estimation method based on an enhanced search coil architecture. The proposed method addresses key limitations of conventional search coil techniques, which often lack inherent startup mechanisms and require auxiliary strategies. By relying solely on search coil signals, without the need for current sensors, the system accurately detects the initial rotor angle, enabling reliable and smooth startup. In contrast to conventional sensorless methods that rely on voltage and current for flux linkage estimation, the search coil approach can directly obtain flux linkage and achieve accurate and stable rotor position estimation through active flux linkage calculation. These features enable seamless and sensorless operation from standstill to high speed. To validate the system’s effectiveness, comprehensive experimental evaluations were conducted, including comparisons with widely adopted sensorless techniques. Performance was assessed across key metrics, including current harmonics, efficiency, and load-handling capability. The results confirm that the proposed search coil-based system offers superior accuracy, robustness, and operational stability across the entire speed range. In addition, the enhanced search coil design improves overall system resilience, providing a solid foundation for future advancements in motor drive technology.